A Multicenter Cross Sectional Study to Evaluate the Role of Duodenal Bulb Biopsy in the Diagnosis of Celiac Disease - Muhammad Aasim Khan, Mohammad Hanif, Kapeel Raja, Naeem Abbas Gilani, Amanullah Khokhar, Amjad Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: A systemic immune disorder elicited by dietary gluten in people who are genetically predisposed to it is referred to as a celiac disease. D1 had been ruled out as a biopsy site due to concerns about Brunner’s glands, peptic duodenitis, gastric metaplasia, and presumed reduced villous height. Due to histological confounding factors, the duodenal bulb (D1) as a biopsy site was traditionally avoided. The present study aimed to assess the duodenal bulb biopsy role in the diagnosis of celiac disease. Methodology: This multicenter cross sectional study was conducted on 108 celiac disease patients in the department of Gastroenterology, Bacha Khan Medical Complex, Swabi, North West General hospital Peshawar and Pir Abdul Qadir Shah Jilani Institute of Medical Science Gambat Khairpur, Sindh from September 2020 to July 2021. All the celiac disease patients were clinically symptomatic and had anti-tissue transglutaminase (anti TTG IgA) positive antibodies. Endoscopically, six mucosal biopsies were taken from each patient, four each from the distal duodenum and two additional biopsy separately labelled was taken from bulb. Modified Marsh grading was used for morphological grading. Results: Of the total 108 Celiac disease patients, 60 (55.6%) were females and 48 (44.4%) were male patients. the overall mean age was 32.62±6.4 years. Prior to diagnosis of Celiac disease, symptoms median duration was 5.4 years with a range of 6 months to 40 years. The most prevalent clinical presentation were iron deficiency anemia 43% (n=46) and chronic diarrhea 32% (n=35) respectively. Other clinical presentation were chronic pain abdomen, infertility, short stature, and cirrhosis. Elevated TTG of 117.1 ± 49.82 U/ml was measured in all the patients with a range of 20 to 250 U/ml. The incidence of similar and different modified Marsh grade was in 66 (61.1%) and 42 (58.9%) respectively at both site. Out of 42 different modified March grade patients, higher mucosal atrophy in bulb and descending duodenum showed higher grade in 16 and 26 patients respectively. Isolated bulb involvement was seen in nine patients. Due to bulb biopsy, Celiac disease diagnosis was correctly done in these patients. Conclusion: The present study supported the villous atrophy and intraepithelial lymphocytosis patchy nature in biopsy specimens of celiac disease. The diagnosis of celiac disease improved with inclusion of duodenal bulb biopsies in our sampling protocol. Celiac disease patchy nature and distribution demonstrated different Marsh grades in different biopsy sites. The celiac disease diagnostic yield is increased by combining the bulb and the descending duodenum biopsy.